Goldenhar`s syndrome – case report - Poppe, Ewa; Bandzul, Krzysztof; Komaszyło-Spalińska, Katarzyna; Florczyk, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
oldenhar`s syndrome is a very rare, multiple, developmental disease, with characteristic oculo-auriculo-vertebral triad of abnormalities. Ophthalmological changes are mainly: microphthalmia or anophthalmia and rarely, coloboma of upper eyelid or coloboma of optic nerve head. The aim of the article is to present the case of anophthalmia in the new-born child with phenotype of Goldenhar`s syndrome.